VALIDATED REVERSED-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR THE ESTIMATION OF TETRABENAZINE IN SELF-NANO EMULSIFYING DRUG DELIVERY SYSTEMS - SHASHI; PANDEY, NARENDRA KUMAR; KUMAR, BIMLESH; SINGH, SACHIN KUMAR; BAGHEL, DILEEP SINGH; SUDHAKAR, KALVATALA; SINGH, SAURABH (International Journal of Applied Pharmaceutics, 2024)
Objective: Self-Nano-Emulsifying Drug Delivery System (SNEDDS) of tetrabenazine (TBZ) was analysed using reverse-phase high-performance liquid chromatography. Methods: Optimized chromatographic condition was consisted of Acetonitrile (ACN) and 0.1% v/v formic acid in the ratio of 90:10 as a mobile phase in isocratic mode at 25±1 °C. In this C-18 (250 mm×4.6 mm, 5 µm) column was used and absorbance was recorded at 283 nm. Results: The compound was eluted at a flow rate of 1.0 ml/min and retention time (RT) was observed as 4.34±0.03 min. TBZ showed linearity over 2-10 µg/ml conc. and the value of regression was obtained as 0.9992. The developed method was found precise due to Percentage Relative Standard Deviation (%RSD) was less than 2 %. On the other hand, 0.31 and 0.96 were investigated value for Limit of Detection (LOD) and Limit of Quantification (LOQ), respectively. Conclusion: The method adopted was found to be robust and can be apply for the determination of drug in different oil, surfactants and co-surfactants for the calculation of drug loading of pharmaceutical product formulation.